Language Shift as Cultural Memory Loss: Quantifying the Erosion of Ethnobiological Knowledge across Three Generations in an Endangered Language Community - Muhammad Ridwan; Belay Sitotaw Goshu; Wan Nurul Atikah (Britain International for Academic Research (BIAR-Publisher), 2026)
Approximately 40% of the world’s 7,000 languages are endangered, with many located in biodiversity hotspots. Language shift may accelerate the loss of traditional ecological knowledge, but quantitative, three‑generation studies are lacking. To quantify the relationship between heritage language shift and ethnobiological knowledge erosion across three generations in an endangered language community. Ninety participants (30 grandparents, G1; 30 parents, G2; 30 children, G3) from 30 families completed standardized language proficiency measures (adapted PPVT, oral fluency) and ethnobiological knowledge tasks (free‑listing, species identification and use). Covariates included age, education, and nature contact. Data were analyzed using ANOVA, Pearson correlation, and hierarchical regression. Language proficiency declined significantly across generations (G1: M=42.1/50; G2: 28.4; G3: 12.7; η²=0.67). Ethnobiological knowledge showed a parallel decline (G1: M=38.6/80; G2: 24.3; G3: 9.8; η²=0.68). The bivariate correlation between language proficiency and knowledge was strong (r=0.72, 95% CI [0.61, 0.80], p<0.001). Regression confirmed language proficiency as a unique predictor (β=0.61, p<0.001) after controlling for covariates, explaining 45% of variance in knowledge. Language shift and ethnobiological knowledge erosion are tightly coupled processes, supporting the view that heritage languages serve as critical scaffolds for cultural memory. Rapid intergenerational loss (70% vocabulary, 88% knowledge) within two generations indicates a biocultural emergency. Integrated interventions—community‑based language revitalization, heritage‑language environmental education, and biocultural conservation policies are urgently needed to preserve both linguistic and ecological diversity.